Anti-Müllerian hormone serum level and other markers associated with pregnancy outcome in oocyte donation - Delesalle, Anne-Sophie (Reprod Biol Endocrinol, 2016)
BACKGROUND: Oocyte donation is a medical technique used principally for woman with ovarian failure. Optimizing donor recruitment is essential to obtain the best results with this technique. Understanding how donor parameters influence outcome for the recipients is fundamental. The aim of this study was to determine whether clinical and/or biological parameters in the donors influence the chance of pregnancy in recipients. Our objective was also to verify whether the outcomes of controlled ovarian stimulation (COS) are predictive of pregnancy in the recipients. METHODS: A retrospective observational study was conducted in the Department of Reproductive Medicine in the Lille University Hospital. Between September 2005 and April 2014, COS was performed in 145 donors for 308 recipients’ cycles. We compared the cycles whose outcome was pregnancy to the cycles without pregnancy. Quantitative variables were compared using the nonparametric Mann–Whitney test. Qualitative variables were compared using a Chi-2 test or Fisher exact test, according to the numbers. Covariance analysis was performed to adjust for potential confounding factors. RESULTS: The donors who produced at least one pregnancy had a mean baseline serum anti-Müllerian hormone (AMH) level significantly higher than those who did not (p = 0.001). The mean antral follicle count did not differ between the 2 groups. After covariance analysis controlling for the number of couples attributed to a given donor, this difference remained significant (p = 0.029). Mature follicle number, estradiol serum level at the trigger day, number of mature oocytes and embryo number were significantly higher in the donors who produced pregnancy. CONCLUSION: Serum AMH level is associated with pregnancy outcome after oocyte donation.